Sepedi home language for Khelobedu-L1 learners: Whose home language is it? A language dilemma - Tsebo Ramothwala (Literator)
Learners whose languages were not fortunate enough to be elevated to official status (those which can be used as languages of learning and teaching [LoLTs]) are compelled to take one of the official languages as a ‘home language.’ In most cases, what is taught as a home language in South African schools is totally different from what learners speak at home. In such a case, learners may be at a disadvantage as they will be taught, assessed as native speakers and expected to demonstrate linguistic abilities of native speakers. This study was envisaged to address this language dilemma in the context of Khelobedu-L1 learners in Bolobedu South. The study employed both qualitative and quantitative approaches, with a case study design. Data were gathered through questionnaires and focus group interviews with 60 learners from the two selected high schools in Bolobedu South. Content analysis was used to analyse the data.